Distribution, risk assessment, and quantitative source apportionment of heavy metals in surface sediments from the shelf of the northern South China Sea. (February 2023) - Cai, Pengjie; Cai, Guanqiang; Yang, Jingsui; Li, Xuejie; Lin, Jie; Li, Shun; Zhao, Li
Abstract: The concentration of heavy metals (Cu, Pb, Zn, Cr, Co, and Ni) from 421 sediment samples from the shelf of the northern margin of the South China Sea (SNSCS) was analyzed. The heavy metal content and calculated potential ecological indicators ( E r i  < 40 and RI  < 160) indicate that there is low potential ecological risk of heavy metal pollution in the SNSCS. The mean effects range-median quotient (M-ERM-Q) and hazard quotient (HQ) values of sediment toxicological characteristics indicate that heavy metals are a potential toxicological risk. The high-risk area is mainly distributed in the southwest of the nearshore SNSCS. The positive matrix factorization (PMF) analysis results showed that major contributors to heavy metal pollution were natural sources and anthropogenic activities in the SNSCS. The government should pay particular attention to the monitoring of heavy metals in the nearshore southwest of the SNSCS. Graphical abstract: Unlabelled Image Highlights: The enrichment of heavy metals is controlled by the Pearl River-derived mud belt. The high-risk areas are mainly distributed in the nearshore southwest of the SNSCS. Natural and anthropogenic sources are the main effects of heavy metals in SNSCS.